Grassroots Dissemination of Research in Africa : Collecting and Connecting - Easton, Peter (World Bank, Washington, DC, 2012)
The note examines methods for grassroots dissemination, from results of African research on the themes of decentralization and local capacity building, but in a manner that would include both the disseminators, and targeted audiences, to critique the studies, analyzing related experiences, and drawing practical policy conclusions. The project "Achieving Basic Education and Literacy" (ABEL), was based on studies conducted between 1996-98 by teams of African researchers in an innovative approach - subcontracting - on a series of topics, drawn from priority research targets, established by the Association for the Development of Education in Africa (ADEA), basically a consortium of African Ministers of Education, and donor agencies. Subjects included the acquisition of skills in the informal sector; practical uses of Koranic literacy; means of building competencies in women's cooperatives; new formulas for nongovernmental organizations-government cooperation in education; and, experiments in informal primary schooling. Results from Benin are presented as a case study: only twenty one percent of member entities were women-directed enterprises. Efforts of self-evaluation stirred neighboring countries to identify reasons preventing achievement of autonomy: lack of training, and weak financial management. This approach evolved into a means for social marketing, action research, and innovation dissemination. This style of dissemination was also developed in other countries, and it is creating a favorable environment for policy decisions, and forms of collaboration.